Frequent hepatic steatosis in amyotrophic lateral sclerosis: Implication for systemic involvement. Issue 2 (14th November 2014) - Nodera, Hiroyuki; Takamatsu, Naoko; Muguruma, Naoki; Ukimoto, Kazuhiro; Nishio, Susumu; Oda, Masaya; Izumi, Yuishin; Kaji, Ryuji
Abstract: Background: Abnormal energy metabolism has been reported in amyotrophic lateral sclerosis (ALS) that broadens the concept of ALS as a systemic disease. Dyslipidemia is likely to reflect the clinical outcome in ALS. Aim: To study whether evidence of dysmetabolism can be detected non‐invasively by imaging study, such as liver sonography. Methods: Abdominal sonography, lipid profiles and liver enzymes were obtained in three groups of individuals: (i) the patients with ALS; (ii) other neurodegenerative diseases; and (iii) asymptomatic dyslipidemic persons. The sonographic steatosis grade was determined by a blinded technician. Statistical tests including one‐wayanova with post‐hoc test, multiple linear regression were carried out. Results: The lipid profiles and liver enzymes were similar between the ALS and dyslipidemic groups. The disease control group had lower low‐density lipoprotein, low‐density lipoprotein‐to‐high‐density lipoprotein ratio and triglyceride than other groups. Hepatic steatosis was present in 76% of ALS patients, 19% of the disease control and 38% of the dyslipidemic group ( P < 0.001 vs ALS). Multivariate analysis showed that only the patient group was correlated to the sonographic score. Conclusion: The present study showed that hepatic steatosis is frequent and a unique phenomenon in ALS among neurodegenerative diseases. Hepatic steatosis might be a sensitive marker for dysmetabolism in ALS.